A Critical Review on the Theological Argument Proving “Divine Will” - Seyyed Muhammad Hosseini Hekmat; Taha Agah (آموزه‌‌های فلسفه اسلامي, 2022)
Theologians in proving the will of God (the divine will) use an argument based on certain preliminaries (premises) and principles (foundations) that have serious problems. These problems are noticed by scholars who have different principles but have accepted and cited this argument. Summary of the argument: There are only some objects among the possible existences (contingent beings) and these objects are created at a certain time. Allocating existence to them and allocating them to their specific time requires an individualizer (Arabic: مخصّص, specificative, specificator, particularizer). This individualizer (specificative), which cannot be knowledge or power, proves another attribute for God, called will. This argument, which is formed in Ashʿarism (Arabic: الأشعریة: al-ʾAshʿarīyah, or Ashʿarī) and despite the fundamental and content problems by some Mu'tazilism (Arabic: المعتزلة al-muʿtazilah) theologians, Imāmiyyah and some scholars have repeated it, have some problems such as preference of one thing over the other without a justified cause undue preference (Arabic: ترجیح بِلا مرجِّح, distinction without a difference), the temporal contingency of the origination of the world, the allocation of will to material and temporal affairs, the possibility of divine will, etc. In addition, there are some problems in the completeness and correctness of this argument, including internal conflict, the lack of exclusiveness of the individualizer (specificative) in the will, the possibility of generalizing the characteristics of the will to knowledge and power, and as a result, the possibility of replacing these two attributes as the individualizer (specificative). We intend in this article to prevent the mistakes caused by this argument through examining these problems and criticizing its argument.